ISLAMIC BUSINESS ETHICS IN TECHNOLOGY BASED BUSINESS - Ismail Halim; Fauzia Fauzia; Nurul Afni; Pusfa Farida; Supriadi Supriadi (STIESA Press, 2022)
With this technological advancement, there are so many types of businesses that have sprung up such as startups and fintech (financial technology), where business people use more technological advances such as the use of the Internet of Things (IoT), Big Data, Artificial Intelligence/AI (Artificial Intelligence), as well as blockchain in running its business. With technological advances in this business, do not forget that there are ethics in running it. In Islam, ethics in online business (technological advances) have been regulated, such as individual data privacy, public data transparency, application process accountability, and including halal financial services. In line with the two types of businesses in finance, there are also types of businesses in buying and selling such as e-commerce and marketplaces. Examples of these types of businesses are Bukalapak, Tokopedia, Shopee and so on. Business ethics in buying and selling online is also regulated in Islam such as; (a) goods/services are traded in accordance with specifications, (b) there is an agreement (ijab and qabul) between the seller and the buyer, (c) upholding trust among transaction actors, (d) avoiding transactions prohibited by sharia, (e) provide good service to consumers. (f) not taking or stealing property belonging to others, (g) using a contract according to the type of transaction carried out, and (h) products/services being traded halal.